2020
DOI: 10.1016/j.psychres.2020.113297
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with mental illness in hospital discharged patients infected with COVID-19 in Wuhan, China

Abstract: The coronavirus disease 2019 (COVID-19) pandemic can have a profound impact on the mental health of patients who survived the illness. However, little is known about the prevalence rate of mental health disorders among hospital discharged COVID-19 patients and its associated factors. A cross-sectional survey of hospital discharged patients was conducted April 11-22, 2020 in Wuhan, China (where the pandemic began). 675 participants completed the survey, including 90 (13.3%) medical staff (physicians and nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
231
11
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(268 citation statements)
references
References 20 publications
19
231
11
7
Order By: Relevance
“…This is detrimental to their self-esteem associated with the social state (Rubin & Hewstone, 1998), further leading to a negative appraisal of their social psychological in-group and thus creating tension and worry (Cassidy et al, 2004). Empirical evidence has shown that social stigma and discrimination due to COVID-19 will exacerbate the negative emotions and evoke severe anxiety (Liu et al, 2020;Ma & Miller, 2020). Therefore, the first hypothesis was proposed: Anxiety and well-being.…”
Section: Proposed Research Frameworkmentioning
confidence: 99%
“…This is detrimental to their self-esteem associated with the social state (Rubin & Hewstone, 1998), further leading to a negative appraisal of their social psychological in-group and thus creating tension and worry (Cassidy et al, 2004). Empirical evidence has shown that social stigma and discrimination due to COVID-19 will exacerbate the negative emotions and evoke severe anxiety (Liu et al, 2020;Ma & Miller, 2020). Therefore, the first hypothesis was proposed: Anxiety and well-being.…”
Section: Proposed Research Frameworkmentioning
confidence: 99%
“…Actually, a “tsunami of psychiatric illness” is being predicted and actions such as calling for a special research topic and accelerating the manuscript review process have been taken to deal with the lacking of useful information in the mental health crisis ( Tandon, 2020 ). Though some studies assessed the prevalence of depressive symptoms and potential influencing factors in hospitalized ( Ma et al, 2020 ) and discharged ( Liu et al, 2020 ) COVID-19 patients, these results might be misleading due to limited sample size. Thus, in this letter, we aimed to provide a rapid meta-analysis of the prevalence of depressive symptoms in COVID-19 patients and potential influencing factors based on published studies which might be the reference for mental health intervention during the epidemic.…”
mentioning
confidence: 99%
“…Eight cross-sectional studies were included after selection involving 2206 individuals with 1040 cases with depressive symptoms ( Guo et al, 2020 ; Hu et al, 2020 ; Liguori et al, 2020 ; Liu et al, 2020 ; Ma et al, 2020 ; Nie et al, 2020 ; Yuan et al, 2020 ; Zhang et al, 2020 ), among which two studies considered cured patients discharged from the hospital ( Liu et al, 2020 ; Yuan et al, 2020 ). One study ( Liguori et al, 2020 ) came from Italy while the others were all from China.…”
mentioning
confidence: 99%
See 2 more Smart Citations